2021
DOI: 10.3390/antiox10050802
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs and Oxidative Stress: An Intriguing Crosstalk to Be Exploited in the Management of Type 2 Diabetes

Abstract: Type 2 diabetes is a chronic disease widespread throughout the world, with significant human, social, and economic costs. Its multifactorial etiology leads to persistent hyperglycemia, impaired carbohydrate and fat metabolism, chronic inflammation, and defects in insulin secretion or insulin action, or both. Emerging evidence reveals that oxidative stress has a critical role in the development of type 2 diabetes. Overproduction of reactive oxygen species can promote an imbalance between the production and neut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 113 publications
(125 reference statements)
0
12
0
Order By: Relevance
“…Growing evidence suggests that hyperglycemia in T2D can enhance the production of reactive oxygen species (ROS), which leads to excessive oxidative stress [ 33 ]. On the other hand, oxidative stress plays a vital role in the development and pathogenesis of T2DM [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence suggests that hyperglycemia in T2D can enhance the production of reactive oxygen species (ROS), which leads to excessive oxidative stress [ 33 ]. On the other hand, oxidative stress plays a vital role in the development and pathogenesis of T2DM [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is already proven that some miRNAs could influence oxidative stress through the modulation of gene expression of antioxidant enzymes, for example SOD [ 80 ]. Since altered regulation of miRNA is associated with oxidative stress, the miRNA expression restoration to normal values may lead to a new therapeutic approach to prevent oxidative damage [ 83 ]. LaPierre et al documented the influence of miRNAs on b-cell function in different metabolic conditions [ 84 ].…”
Section: Micro-ribonucleic Acidsmentioning
confidence: 99%
“…Regarding T2D, it is interesting to pay attention to the miRNA-200 family, which is important for redox regulation and could be positively modulated by hydrogen peroxide (H 2 O 2 ). Hyperglycemia leads to oxidant protein modification and formation of advanced glycation end products (AGE), which could be modified by different miRNAs [ 83 ]. MitomiRs are recently discovered miRNAs situated in mitochondria and are able to regulate mitochondrial function connected with fatty acid oxidation, which is also linked to oxidative stress [ 83 ].…”
Section: Micro-ribonucleic Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Growing evidence indicates that T2D could be a severe metabolic condition affecting more than 400 million individuals globally, and predicts that this number might surpass 600 million by 2040. 2,3 Statistical evidence has demonstrated that T2D is a top 10 cause of death globally, killing over 1.5 million people worldwide. 4 Moreover, T2D is the third most significant risk factor for worldwide premature mortality due to inflammation, hyperglycemia, and oxidative stress.…”
Section: Introductionmentioning
confidence: 99%